Norwegian and Russian Mining and Mining Communities in Monica Kristensen’s Oeuvre - Wærp, Lisbeth Pettersen (Poljarnyj vestnik, 2022)
Monica Kristensen is a Norwegian glaciologist, meteorologist, polar explorer and author of fiction (crime novels) and nonfiction (about expeditions, Svalbard, The Kings Bay Affair, and Roald Amundsen). In her altogether five crime novels, all of which take place in Svalbard, the plot is inextricably bound to place, i.e. to the Arctic. In two of her five crime novels, Kullunge and Den døde i Barentsburg, crucial parts of the action take place in the coal mines of Longyearbyen and Barentsburg. In her documentary book about the Kings Bay Affair she investigates the terrible mining accident in 1962 at Kings Bay mines that killed 21 miners. In this article I examine the literary construction of these specific places – the Arctic and the coal mines, or, the coal mines in the Arctic – in these three books, as well as the related political, ethical and existential questions of settlement and living conditions.